The effect of media combinations on nutrient load in float trays and tobacco (Nicotina tabacum L.) seedling survival counts - Masaka, Johnson; Ndidzano, K. (Academic Journals, 2021)
The main objective of the study was to determine nutrient depletion dynamics in various media combinations and their effect on tobacco seed germination and seedling survival count. Study results showed that the presence of pine bark in the media mix strongly monitored soluble cation nutrient and phosphate holding capability of the container media. When the content of pine bark in the media combination increased from 25% (T2) through 50% (T3), 75% (T4) to 100% (T5) in the pine bark-coal rubble mix there was a corresponding elevation of cation concentrations in the media from an average of 10.73 to 15.76, 33.04 and 45.72 meq/100 g, respectively. The enhanced nutrient holding ability of pine bark-based media mixtures conferred such combinations the highest tobacco seedling germination and survival. The lowest seedling emergence and survival counts were observed in float trays filled with media combinations dominated by coal rubble. Germination and survival counts improved with reduction in coal rubble component in the media. Research studies elsewhere have recommended replacing coal rubble with sand because of similarities in their physical properties. In this study, results show that replacing coal rubble with sand in the media dwarfs combined nutrient loads by 15.6, 19.1 and 0.9% at 7, 35 and 42 DAS, respectively while it amplifies nutrient content by 4.8% at 21 DAS. Replacing coal rubble with sand in a 50/50 combination with pine bark significantly enhances the phosphate carrying capacity of the media.